Cdc45 is limiting for replication initiation in humans. Issue 7 (2nd April 2016) - Köhler, Carsten; Koalick, Dennis; Fabricius, Anja; Parplys, Ann Christin; Borgmann, Kerstin; Pospiech, Helmut; Grosse, Frank
ABSTRACT: Cdc45 is an essential protein that together with Mcm2-7 and GINS forms the eukaryotic replicative helicase CMG. Cdc45 seems to be rate limiting for the initial unwinding or firing of replication origins. In line with this view, Cdc45-overexpressing cells fired at least twice as many origins as control cells. However, these cells displayed an about 2-fold diminished fork elongation rate, a pronounced asymmetry of replication fork extension, and an early S phase arrest. This was accompanied by H2AX-phosphorylation and subsequent apoptosis. Unexpectedly, we did not observe increased ATR/Chk1 signaling but rather a mild ATM/Chk2 response. In addition, we detected accumulation of long stretches of single-stranded DNA, a hallmark of replication catastrophe. We conclude that increased origin firing by upregulated Cdc45 caused exhaustion of the single-strand binding protein RPA, which in consequence diminished the ATR/Chk1 response; the subsequently occurring fork breaks led to an ATM/Chk2 mediated phosphorylation of H2AX and eventually to apoptosis.